2019
DOI: 10.1097/lgt.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

International Anal Neoplasia Society Guidelines for the Practice of Digital Anal Rectal Examination

Abstract: The aim of the study was to develop recommended techniques and quality assurance metrics for the practice of Digital Anal Rectal Examination (DARE). Materials and Methods: The International Anal Neoplasia Society undertook a literature review and, using the AGREE II technique, developed guidelines for performing DARE. Results: A consensus was formed regarding the optimum conditions and characteristics of DARE. Several Quality Assurance metrics were developed. Conclusions: Digital Anal Rectal Examination is a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 35 publications
0
65
0
1
Order By: Relevance
“…The fact that HPV16 E6 antibody seropositivity may have utility for screening for anal cancer (44) as well as OPC is an important consideration for appropriate triage/evaluation of biomarker positive individuals. Like HPV-OPC, anal cancer is another HPV-related cancer for which optimal screening approaches remain unclear (45)(46)(47), and research suggests these same HPV DNA biomarkers (DEIA and Cobas) also have high specificity and moderate sensitivity for anal precancer (48,49). The low prevalence of E6 antibodies, even among the high-risk group of HIVinfected individuals and men who have sex with men in this study, supports a possible higher positive predictive value of this marker in highlighting those as risk.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that HPV16 E6 antibody seropositivity may have utility for screening for anal cancer (44) as well as OPC is an important consideration for appropriate triage/evaluation of biomarker positive individuals. Like HPV-OPC, anal cancer is another HPV-related cancer for which optimal screening approaches remain unclear (45)(46)(47), and research suggests these same HPV DNA biomarkers (DEIA and Cobas) also have high specificity and moderate sensitivity for anal precancer (48,49). The low prevalence of E6 antibodies, even among the high-risk group of HIVinfected individuals and men who have sex with men in this study, supports a possible higher positive predictive value of this marker in highlighting those as risk.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known if regular anal self-examination will result in the detection of primary anal syphilis, and therefore studies evaluating the e cacy of anal self-examination for syphilis detection are required. Anal self-examination has been studied among HIV-positive MSM aged over 50 for anal cancer detection and was shown to be a cost-effective screening method in MSM living with HIV (12,14,19,20). Our research shows men who practise receptive or versatile anal sex may be willing to adopt such a screening practice if it was recommended and came with education on what to look for during the examination, particularly signs of syphilis in the anus.…”
Section: Discussionmentioning
confidence: 84%
“…Anal self-examination, although a new concept for syphilis detection, is a practice promoted among MSM aged over 50 who are living with HIV to detect early anal cancer (12)(13)(14). A previous qualitative study among MSM living with HIV suggested that annual digital anal examination is an acceptable approach for anal cancer screening (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst digital anal rectal examination (DARE) is an important first step in the evaluation of all symptomatic patients, this unfortunately has a very limited evidence base and may have significant false-negative rates [7]. In centres with highly trained practitioners, subject to robust quality assurance measures [8], HRA offers the unique ability, like colonoscopy, to detect cancers at an order of magnitude greater than those by palpation at DARE [6].…”
mentioning
confidence: 99%